School furniture ergonomics in prevention of pupils’ poor sitting posture : Ergonomija školskog namještaja u prevenciji lošeg držanja tijela učenika - Alibegović, Aldina (Array, 2020)
Physical and psychological disorders in school-age children, as a consequence of prolonged sitting in class, denote one of the alarming issues of the today’s civilization. Scientific and professional literature pays great attention to the causes and phenomena of postural disorders caused by prolonged sitting, such as musculoskeletal disorders and back pain (MSD/BP). This phenomenon in children is increasingly correlated with school furniture design. School furniture, especially the chair and desk, are one of the most important factors to achieve the right body posture of pupils during school education. Despite this, not much attention is paid to the ergonomic requirements in furniture design, which are a prerequisite for good health, motivation improvement and learning of students. The objective of this paper is to show the impact of unmatched school furniture on the development of health problems and poor pupils’ posture through a review of scientific literature and previous studies concerning the issue. The results include a comparison of ten papers published in the period from 2004 to 2017 in Finland, Greece, Croatia, Slovenia, Nigeria, Brazil, Iran, Belgium, United Kingdom and India. Various databases have been used, including Pub Med, Google Scholar, Medline, Hrčak, Dabar, Science Direct and Science Citation Index. By reviewing the previous research of the selected authors dealing with sitting posture in school, an insight was gained into the effect of inadequate body postures on pupils’ health that could be used as guidance for new school furniture design.